2020
DOI: 10.21203/rs.3.rs-112215/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

β-Ecdysterone Prevents LPS-Induced Osteoclastogenesis by Regulating NF-κB Pathway in Vitro

Abstract: BackgroundLipopolysaccharide (LPS), a bacteria product, plays an important role in orthopedic diseases. Drugs that inhibit LPS-induced osteoclastogenesis are urgently needed for the prevention of bone destruction.MethodsIn this study, we evaluated the effect of β-ecdysterone (β-Ecd), a major component of Chinese herbal medicines derived from the root of Achyranthes bidentata BI on LPS-induced osteoclastogenesis in vitro and explored the mechanism underlying the effects of β-Ecd on this.ResultsWe showed that β-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…Vitexin inhibited osteoclast differentiation and osteolysis ( 28 ), and Wang et al ( 84 ) revealed the inhibitory activity of linarin on osteoclastogenesis through the RANKL-induced NF-κB pathway. In addition, ecdysterone, another active compound in MFR, prevented LPS-induced osteoclastogenesis ( 86 ). Ursolic acid has also been shown to inhibit osteoclastogenesis and titanium particle-induced osteolysis ( 87 ).…”
Section: Discussionmentioning
confidence: 99%
“…Vitexin inhibited osteoclast differentiation and osteolysis ( 28 ), and Wang et al ( 84 ) revealed the inhibitory activity of linarin on osteoclastogenesis through the RANKL-induced NF-κB pathway. In addition, ecdysterone, another active compound in MFR, prevented LPS-induced osteoclastogenesis ( 86 ). Ursolic acid has also been shown to inhibit osteoclastogenesis and titanium particle-induced osteolysis ( 87 ).…”
Section: Discussionmentioning
confidence: 99%